A framework for untangling linnaean names based on plumier’s nova plantarum americanarum genera: Revised typification of duranta erecta - Moroni, Pablo Daniel (2018)
The typification of the Linnaean name Duranta erecta is revised. The previous lectotypification by Caro, who proposed a Burman illustration in Plantarum americanarum as lectotype, must be superseded since that element was not available to Linnaeus before the publication of the first edition of Species plantarum. We conclude that Boerhaave’s tracing no. 212 of Plumier’s original drawing, currently held at the Library of the Rijksuniversiteit in Groningen, The Netherlands, was studied by Linnaeus during his stay in Leiden. As a result, this drawing is therefore selected as lectotype of the species name.